2006
DOI: 10.1111/j.1083-6101.2006.00325.x
|View full text |Cite
|
Sign up to set email alerts
|

Remembering Our Shared Past: Visually Framing the Iraq War on U.S. News Websites

Abstract: This exploratory study analyzes how United States news websites visually portray ongoing (contemporaneous) events and examines their potential role in shaping collective memory by commemorating past (resurrected) events through anniversary retrospectives. A content analysis of 526 images on the home pages of 26 mainstream news sites indicates that during the first five weeks of the Iraq War, the visual emphasis shifted from the official U.S. war machine to the more personal face of those touched by war, both A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 55 publications
1
46
0
4
Order By: Relevance
“…Data were also collected from the same Web sites approximately 1 month later (Thursday, October 18, 2007) in an effort not to bias the results due to a significant health-related event in a given month (e.g., Cervical Cancer Awareness Month is in January, September is Prostate Cancer Awareness Month). Riffe, Lacy, and Fico (1998) have discussed the difficulty of sampling Internet content, and sampling stratification in previous content analyses of online news varies by author (Bucy, 2004;Hoffman, 2006;Lim, 2006;Schwalbe, 2006). Although the most recent research regarding sampling of online news found that two constructed weeks of content are needed to accurately represent online news (Hester & Dougall, 2007), this method is recommended when examining online news as a whole, instead of one particular type of news story, such as "science" or "health."…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Data were also collected from the same Web sites approximately 1 month later (Thursday, October 18, 2007) in an effort not to bias the results due to a significant health-related event in a given month (e.g., Cervical Cancer Awareness Month is in January, September is Prostate Cancer Awareness Month). Riffe, Lacy, and Fico (1998) have discussed the difficulty of sampling Internet content, and sampling stratification in previous content analyses of online news varies by author (Bucy, 2004;Hoffman, 2006;Lim, 2006;Schwalbe, 2006). Although the most recent research regarding sampling of online news found that two constructed weeks of content are needed to accurately represent online news (Hester & Dougall, 2007), this method is recommended when examining online news as a whole, instead of one particular type of news story, such as "science" or "health."…”
Section: Sampling Proceduresmentioning
confidence: 99%
“…Korostamisen kannalta huomio kiinnittyy erityisesti lehtijutun erottuvimpiin osiin, kuten otsikkoon, ingressiin, tekstin alkuun, kuvatekstiin ja pääkuvaan (Tankard 2001, 100). Kuvien osalta kuvan kohteen valinta, toimitukseen lähetettävien ja julkaistavien (sekä pois jätettävien) kuvien valinta, kuvan koon määrittely ja asemointi lehteen sekä monet kuvaajan tekemät tuotannolliset ratkaisut vaikuttavat siihen, mitkä aspektit kustakin teemasta korostuvat (Coleman 2010;Messaris & Abraham 2001;Schwalbe 2006) ja millaisia käsitteellisiä kytköksiä mediaesitykseen rakentuu (Scheufele & Tewksbury 2007). Varsinkin suurikokoiset kuvat kiinnittävät nopeasti lehden lukijan huomion (Garcia & Stark 1991;Knobloch ym.…”
Section: Kehystäminen Ja Mediakuvatunclassified
“…In an investigation of visual frames of the first, second, and third anniversaries of the Iraqi invasion as a "past (resurrected) event," Schwalbe (2006) found that these visual frames emphasize "the human face of war" rather than the war machine itself.…”
Section: Framing and The "Visual Turn"mentioning
confidence: 99%
“…Thus, content analysis of visual data is quite common in visual framing studies that "inductively" or "deductively" identify the visual frames in photographs (e.g., Fahmy, 2004Fahmy, , 2007Messaris & Abraham, 2001;Schwalbe, Silcock, & Keith, 2008). For instance, Schwalbe (2006) preferred to inductively glean visual frames from the actual photographs of the Iraqi war, rather than analyze the visual frames depicted in the data deductively. Similarly, Parry's (2010) analysis of british press photography used a similar "inductive" approach and then had independent coders code the data for content analysis.…”
Section: Framing and The "Visual Turn"mentioning
confidence: 99%